Síntese, caracterização e avaliação da atividade fotocatalítica de TiO2 modificado com nitrogênio e prata - Silva, Tatiana Aparecida da (2015)
In this work, catalysts based on titanium dioxide doped with silver and/or nitrogen were synthesized in order to obtain oxides with high photocatalytic activity and photoactivation under visible radiation. The semiconductors were obtained by homogeneous precipitation varying synthesis parameters (concentration and dopant order of addition) and heat treatment (furnace or hydrothermal). In order to understand the relationship between structural, morphological, electronic and photocatalytic activity of the studied oxides various characterization techniques were applied, including X-ray diffraction (XRD), diffuse reflectance spectroscopy, specific surface area (BET), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM) and Raman spectroscopy. The photocatalytic potential of the catalysts was analyzed by photodegradation tests of azo dye Tartrazine and hydrogen production essays. Raman spectroscopy, X-ray diffraction and Rietveld refinement revealed crystalline catalysts with coexistence of anatase and brookite phases. It was also observed the anatase predominance in all oxides. The semiconductors exhibited high surface areas and crystallite size, between 5 and 14 nm, and showed to be strongly affected by the concentration of dopants. Furthermore, the observed increase of the catalysts absorption in the visible region by the inclusion of dopants could be attributed by the insertion of intermediate levels between the valence band and conduction band of the oxides. The codoping catalysts exhibited an increase in photocatalytic activity when compared to doped oxides and TiO2-P25. This increment could be related to the synergy between the used dopants, providing a more efficient charge separation and consequent retardation of electron/hole recombination. The ascending order of photocatalytic activity of evaluated materials was TiO2 < NTiO2 < AgTiO2 < AgNTiO2, highlighting the catalyst Ag5N18,5TiO2-2, with 62.1% mineralization and 97.9% discoloration of Tartrazine, in 140 minutes of reaction, and a rate of 42.6 mmol g-1 h-1 hydrogen production, while TiO2 achieve 21.1% mineralization and 49.1% discoloration in the same time interval, and a hydrogen production rate of 6.1mmolg-1 h-1.